APRESIASI MATEMATIKA DITINJAU DARI PERSPEKTIF GENDER PADA SISWA KELAS VIII - Fedi, Sebastianus (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
Abstract: Math Appreciation in Terms of Gender at the eight Grade Students in Poco Ranaka Barat District, East Manggarai. Math appreciation is the conscious judgment about the importance of math in our lives. The higher the appreciation of math, the higher of the learning motivation will be. Meanwhile, the experts support difference between female and male on math appreciation, that is  male’s is higher than female. This study was  the descriptive- quantitative research method which examined 114 male and 144 female  out of 560 students at the eigth grade of Junior High School at Poco Ranaka Barat, East Manggarai. By using t test analysis on the average scores, the researcher found out that the students’ math appreciation of the eight class  is at the moderate level, and there is no difference in math appreciation between male and female students.Keywords: math appreciation, genderAbstrak: Apresiasi Matematika Ditinjau dari Gender pada Siswa Kelas VIII Sekecamatan Poco Ranaka Barat, Kabupaten Manggarai Timur. Apresiasi matematika adalah penilaian secara sadar akan peran penting matematika dalam hidup kita. Makin tinggi apresiasi matematika maka motivasi belajar matematika juga makin tinggi. Sementara ada pendapat ahli yang mendukung perbedaan di mana pada urusan yang sulit dan abstrak seperti matematika, apresiasi kaum laki-laki lebih tinggi daripada wanita. Melalui penelitian deskriptif-kiantitatif, dengan  pada nilai rata-rata, yang melibatkan 114 pria dan 114 wanita dari 560 siswa kelas VIII sekecamatan Poco Ranaka Barat, Manggarai Timur, NTT, diperoleh  kesimpulan (1) apresiasi matematika siswa kelas VIII sekecamatan Poco Ranaka Barat berada pada tingkat sedang; dan (2) tidak ada perbedaan tingkat apresiasi matematika antara siswa laki-laki dengan siswa perempuan.Kata kunci: apresiasi matematika, gender